Laïcité and Discontents: Understanding Islamophobia in France - Sellita Sellita; Amalia Hasyim (International Journal Labs, 2025)
Islamophobia has grown significantly in France since President Emmanuel Macron permitted caricatures of the Prophet Muhammad, which outraged Muslim communities. These events have contributed to the perception that Islam threatens French secular values (Laïcité). While France upholds a secular system where state affairs must remain separate from religion, the presence of Muslim immigrants has become a major concern for the French government, which worries about threats to the principle of secularity, as Islam is often viewed as incompatible with liberal French culture[A1]. This research examines the impact of Islamophobia on Muslim communities in France during President Emmanuel Macron's administration, using Constructivism and National Interest theories to analyze how Islamophobia influences Muslim society under Macron's leadership. The study employs qualitative methods and descriptive analysis, with data collected from secondary sources, including news outlets, official websites, and prior research related to Islamophobia in France. The findings indicate that Macron's statements and policies have significantly affected Muslim communities in France, leading to social discrimination, racism, violence, and international boycotts, though the long-term effects of international boycotts require further investigation. The research concludes that the reinforcement of laïcité has been instrumentalized in ways that disproportionately target Muslims, undermining social cohesion and human rights. The findings highlight the need for policy reforms that balance secular principles with religious freedom and inclusion, as well as greater international awareness of systemic Islamophobia in France.